Reconstructing Pesantren Curriculum in The Digital Era: Integrating Islamic Values and Modern Knowledge - Rohim, Faidhur; Muhamad Jamaludin; Moh. Rian Hidayat (Sunan Kalijaga International Journal on Islamic Educational Research, 2026)
This study examines pesantren curriculum reconstruction in the digital era through the integration of Islamic values and modern knowledge at Miftahul Ulum Wongsorejo Islamic Boarding School. It responds to the gap between the increasing demand for educational digital transformation and the persistence of predominantly traditional curriculum practices in pesantren. The study argues that curriculum reconstruction should not be viewed as replacing Islamic educational identity, but as an adaptive transformation that enables pesantren to meet contemporary educational needs while maintaining their religious foundations. Using a qualitative case study approach, data were collected through interviews, observations, and documentation related to curriculum practices, learning activities, and institutional responses to digital-era challenges. The data were analyzed thematically to identify patterns of curriculum adaptation, value integration, pedagogical change, and implementation constraints. The findings indicate that the curriculum is shifting from a traditional model toward an integrative model. Islamic values and modern knowledge are reflected in contextualized learning practices, although they have not been fully systematized in curriculum planning. Key challenges include limited educators’ digital competence, inadequate technological infrastructure, and concerns about technology’s negative impact on students’ morality and pesantren culture. The study offers practical insight for developing adaptive, value-based, and digitally responsive Islamic education.